Contorted polycyclic aromatic hydrocarbons with two embedded azulene units - Yang, Xuan; Rominger, Frank; Mastalerz, Michael (Angewandte Chemie. International edition, 2019)
Deep Blue! Soluble contorted PAHs with two embedded azulene moieties with different degrees of curvature are synthesized and spectroscopically compared.
Gesehen am 18.01.2021